The Effect of Mindfulness-Based Stress Reduction Therapy on Psychological Well-Being in Moms of Mental Retarded Children at SLB C Dharma Wanita Pare Kediri - Reni Nurhidayah; Nurafia Zuhara (Journal for Quality in Public Health, 2021)
Mothers of mentally retarded children have excessive burdens in caring for their children. This is often stressful. Therefore, various therapies are needed and one of them is mindfulness-based stress reduction therapy. The purpose of this study was to determine the effect of mindfulness-based stress reduction therapy on the psychological well-being of mothers of children with mental retardation. The research design was quasi-experimental with one group pretest posttest approach. The population was all mothers of children with mental retardation in SLB-C Dharma Wanita Pare-Kediri with a sample of 15 respondents taken by purposive sampling technique and using T-test data analysis. From the results of the study, it is known that the average psychological well-being score of mothers in caring for mentally retarded children before the mindfulness-based stress reduction therapy is 80.6 with the lowest score is 78 and the highest is 83, while after that the average score is 117.07 with the lowest score 114 the highest is 123. T-test analysis show of p-value = 0.000 (p-value <0.05,so H0 is rejected). This is due to the provision of mindfulness therapy (full awareness), the mother begins to realize that caring for a child who is experiencing mental retardation is an experience here at this time that must be faced. It was concluded that mindfulness-based stress reduction therapy was effective in improving psychological well-being for mothers of mentally retarded children. It is recommended that the nursing profession adopt mindfulness-based stress reduction therapy to increase psychological well-being for mothers of mentally retarded children.